Impact of Culture in Indian Higher Education on Employability of Students (International Journal of Scientific Research and Management (IJSRM), 2014)
tThe paper analyses the cultural issues affecting employability of students in Indian higher education. The transformation of economy into a knowledge economy creates the need for critical thinking skills in graduates to support the industry to face global competition. However the poor employability of graduates highlights the failure of the system to develop critical thinking skills in the graduates. The paper attempts to analyze cultural factors affecting the performance of the academicians by collecting the data from teachers working in private and public universities. A survey design was used for the study. Private and public universities in northern part of India were selected for the study. It was found that high power distance restricts development of critical thinking skills among graduates leading to poor employability